2021
DOI: 10.3390/cancers13174330
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in Lung Cancer: Actors and Heralds of Tumor Development

Abstract: Lung cancer is a leading cause of cancer-related death worldwide and in most cases, diagnosis is reached when the tumor has already spread and prognosis is quite poor. For that reason, the research for new biomarkers that could improve early diagnosis and its management is essential. Exosomes are microvesicles actively secreted by cells, especially by tumor cells, hauling molecules that mimic molecules of the producing cells. There are multiple methods for exosome isolation and analysis, although not standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 153 publications
(158 reference statements)
0
14
0
Order By: Relevance
“…Exosomes contain massive bioactive molecules that can be delivered to recipient cells and alter their biological behavior. Several studies have shown that exosomes could induce tumor growth and modify cancer cell microenvironment and then promote the tumor’s multiplication, migration, and invasion ( 7 , 21 , 22 ). The concentration of exosomes was quantified using bicinchoninic acid protein reagent kit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes contain massive bioactive molecules that can be delivered to recipient cells and alter their biological behavior. Several studies have shown that exosomes could induce tumor growth and modify cancer cell microenvironment and then promote the tumor’s multiplication, migration, and invasion ( 7 , 21 , 22 ). The concentration of exosomes was quantified using bicinchoninic acid protein reagent kit.…”
Section: Resultsmentioning
confidence: 99%
“…After EMT, epithelial cells acquire a mesenchymal phenotype and lessen intracellular adhesion and proliferative capacity, which in turn enhances the invasion and migration of cancer cells (4). A plethora of studies indicate that exosomes take part in the EMT process of lung cancer by transferring mesenchymal-induced signals, which induce cancer cells to more likely migrate to distant sites (5)(6)(7). Exosomes are biological vesicles that contain a large number of biologically active molecules, such as proteins, mRNAs, and miRNAs (8).…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of the cranial microenvironment and targeted migration of cancer cell exosomes are particularly important for the development of lung cancer brain metastases. In this context, exosomes play an important role in the tumor microenvironment and are directly or indirectly involved in intercellular signal transduction, tumorigenesis, and progression in the tumor microenvironment ( 163 ). For example, exosomes secreted by lung cancer cells contain oncogenes and they target the tumor microenvironment, thus promoting tumor progression ( 164 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of exosomes derived from human cells to examine an individual's health status is an emerging molecular diagnostic (Figure 5, Trams et al, 1981;Johnstone et al, 1987;Sokolova et al, 2011;van der Pol et al, 2014;Greening et al, 2015;Pegtel and Gould, 2019). The focus of the published papers is related to cancer to parse the roles of exosomes in pathophysiology, autophagy, diagnosis, and therapeutic applications (Colletti et al, 2020;Jafari et al, 2021;Kugeratski and Kalluri, 2021;Lakshmi et al, 2021;Sandua et al, 2021;Xu et al, 2021;Zhou et al, 2021). As the exosomes are also synthesized and released from brain cells to blood or CSF through the BBB, alterations in the contents of exosomes may serve as biomarkers to detect the pathological progress of the CNS (Kanninen et al, 2016;Jiang et al, 2019;Vandendriessche et al, 2020;Pinnell et al, 2021).…”
Section: Unique Biomarkers Mirna Biomarkers Referencesmentioning
confidence: 99%